The social conditions of Shatra during the British rule 1918-1921 Prof Dr. Shakir Hussein Dumdum - Dumdum , Prof Dr. Shakir Hussein (Thi Qar Arts Journal, 2023)
This topic deals with the social conditions of Shatra during the British rule 1918-1921. This research came from four basic topics: The first topic was devoted to the British policy and its impact on the nature of the social structure in Shatra. While the second topic touched on the social organizations of the Shatra tribes during the British rule. The third topic dealt with the impact of non-Muslim religious sects in Shatra on social life. The fourth and final topic came to address the aspects of social life in Shatra from education, health, endowments and sports.The research relied on a variety of sources, especially unpublished and published British documents. As well as Arabic, Arabized and foreign books and some published articles.The British domination of Iraq added its political importance mainly to some tribes with a high percentage, this from one side, and from another side the emergence of worthy personalities in these tribes. In Shatra, some personalities appeared on the stage of tribal leadership, so we notice the emergence of more than one sheikh on the leadership of one tribe, and that some of these personalities feel that they have achieved something for their tribe and have a reputation among the tribes. Received 6/4/2023, Accepted 5/8/2023  , Published 30/9/2023.